Use of a High‐Protein Enteral Nutrition Formula to Increase Protein Delivery to Critically Ill Patients: A Randomized, Blinded, Parallel‐Group, Feasibility Trial. Issue 4 (30th December 2020) - Chapple, Lee‐anne S.; Summers, Matthew J.; Bellomo, Rinaldo; Chapman, Marianne J.; Davies, Andrew R.; Ferrie, Suzie; Finnis, Mark E.; Hurford, Sally; Lange, Kylie; Little, Lorraine; O'Connor, Stephanie N.; Peake, Sandra L.; et al.
Abstract: Background: International guidelines recommend critically ill adults receive more protein than most receive. We aimed to establish the feasibility of a trial to evaluate whether feeding protein to international recommendations would improve outcomes, in which 1 group received protein doses representative of international guideline recommendations (high protein) and the other received doses similar to usual practice. Methods: We conducted a prospective, randomized, blinded, parallel‐group, feasibility trial across 6 intensive care units. Critically ill, mechanically ventilated adults expected to receive enteral nutrition (EN) for ≥2 days were randomized to receive EN containing 63 or 100 g/L protein for ≤28 days. Data are mean (SD) or median (interquartile range). Results: The recruitment rate was 0.35 (0.13) patients per day, with 120 patients randomized and data available for 116 (n = 58 per group). Protein delivery was greater in the high‐protein group (1.52 [0.52] vs 0.99 [0.27] grams of protein per kilogram of ideal body weight per day; difference, 0.53 [95% CI, 0.38–0.69] g/kg/d protein), with no difference in energy delivery (difference, −26 [95% CI, −190 to 137] kcal/kg/d). There were no between‐group differences in the duration of feeding (8.7 [7.3] vs 8.1 [6.3] days), and blinding of the intervention was confirmed. There were no differences in clinical outcomes, including 90‐day mortality (14/55 [26%] vs 15/56 [27%]; risk difference, −1.3% [95% CI, −17.7% to 15.0%]). Conclusion: Conducting a multicenter blinded trial is feasible to compare protein delivery at international guideline–recommended levels with doses similar to usual care during critical illness.